2011
DOI: 10.1534/genetics.111.128561
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate Receptor Activates the Lipid Kinase PI3K in Drosophila Motor Neurons Through the Calcium/Calmodulin-Dependent Protein Kinase II and the Nonreceptor Tyrosine Protein Kinase DFak

Abstract: Ligand activation of the metabotropic glutamate receptor (mGluR) activates the lipid kinase PI3K in both the mammalian central nervous system and Drosophila motor nerve terminal. In several subregions of the mammalian brain, mGluR-mediated PI3K activation is essential for a form of synaptic plasticity termed long-term depression (LTD), which is implicated in neurological diseases such as fragile X and autism. In Drosophila larval motor neurons, ligand activation of DmGluRA, the sole Drosophila mGluR, similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…A gene with abundant interactions is thought to make a significant contribution to functional recovery. Some of these genes, such as Myod1, Camk2d and Dmd, have been verified to benefit AChRs structure 30 31 32 . We measured the expression levels of these genes in the normal, ctrl and miR-434-3p + groups using real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gene with abundant interactions is thought to make a significant contribution to functional recovery. Some of these genes, such as Myod1, Camk2d and Dmd, have been verified to benefit AChRs structure 30 31 32 . We measured the expression levels of these genes in the normal, ctrl and miR-434-3p + groups using real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium/calmodulin-dependent protein-kinase II (Camk2d) is a ubiquitous enzyme that modulates the functions of many neuronal proteins in response to changes in intracellular calcium concentrations. Chun-Jen Lin C et al reported that Camk2d enhanced the motor axon diameter and increased the synapse numbers at the larval neuromuscular junction 32 . Moreover, myogenic differentiation (Myod) deletion resulted in major alterations in the organization of the neuromuscular junction and was linked to perturbations in the nuclear localization of β-catenin 31 .…”
Section: Discussionmentioning
confidence: 99%
“…ALK gene mutations are associated with both familial and sporadic neuroblastoma. Downstream signalling cascade of ALK signalling includes AKT, ERK1/2 and STAT3 [ 47 ].Calcium phosphorylates three kinases (AKT, ERK and FAK) that are involved in the cell survival signalling in neuroblastoma ( Figure 3 ) [ 48 , 49 ].…”
Section: Signalling Pathways In Neuroblastoma and Their Dependencementioning
confidence: 99%
“…Flies have two identified glutamate-gated metabotropic receptors (mGluR) (Eroglu et al ., 2003). DmGluRA acts via PI3 kinase, as an autoreceptor with a negative feedback action, at presynaptic terminals of motor neurons (Howlett et al ., 2008; Lin et al ., 2011). DmGluRA is widely expressed in the CNS but the functions of neither of the fly’s two mGluR’s in the CNS is clear (Ramaekers et al ., 2001; Devaud et al ., 2008).…”
Section: Assigning Functions To Structural Networkmentioning
confidence: 99%